(untitled) (Research, Society and Development, 2021)
To compare the efficiency of North Carolina State University medium 23 (NCSU23) and Alpha Minimum Essential Medium (α-MEM) as a base medium, and to evaluate the effects of Anti-Müllerian Hormone (AMH) alone or in combination with Follicle Stimulating Hormone (FSH) on the in vitro development and steroid production of isolated porcine preantral follicles. Porcine secondary follicles were cultured in NCSU23 or α-MEM media for 4 days. Once α-MEM was determined to be the optimal culture medium, secondary follicles were cultured in α-MEM alone or supplemented with FSH (1.5 ng/mL), AMH (50 ng/mL) or the combination of the two hormones. Follicle development was evaluated by measuring follicular growth, morphology and hormone production. There was no difference between the media NCSU23 and α-MEM in terms of follicle survival and growth (P > 0.05). However, at day 2, the antrum formation rate tended to be (P < 0.074) higher in α-MEM than NCSU23. At day 4 of culture, the estradiol and progesterone secretion were higher in α-MEM than NCSU23 (P < 0.01), while the opposite was observed for testosterone (P < 0.01). The addition of AMH and/or FSH did not affect follicular survival and growth. Nevertheless, the secretion of estradiol and progesterone induced by FSH was reduced with AMH (P < 0.01). α-MEM is a more effective base medium than NCSU23 for the in vitro follicular development of pig preantral follicles and AMH reduces the steroid production induced by FSH.